Adsorption characteristics of green 5-arylaminomethylene pyrimidine- 2,4,6-triones on mild steel surface in acidic medium: Experimental and computational approach - Chandrabhan, Verma; Lukman.O, Olasunkanmi; Eno.E, Ebenso; M.A, Quraishi (Elsevier B.V, 2020)
Results in Physics, 8 (2018) 657–670